Diversity of lycopods and ferns of the tropical subdeciduous forest of Hidalgo state, Mexico - Martínez-Cabrera, Dorismilda; Hernández-Hernández, Nubia Neydy; Isidro-Hernández, Benjamín; Hernández-Álvarez, Adriana Gisela; Sánchez-González, Arturo (Instituto de Ecología, A.C., 2018)
Background and Aims: Floristic studies of ferns and lycopods in the tropical forests of Mexico are scarce. The objectives of the present study were to know the richness of both groups in the tropical subdeciduous forest (BTS) of the state of Hidalgo, and compare their composition and richness at the species level with that of other regions of the country with the same type of vegetation.Methods: Collection of plant specimens was carried out in 26 localities of six municipalities with BTS of Hidalgo state. The taxonomic determination was realized up to species level. The taxonomic similarity between municipalities was estimated with cluster analysis (Sørensen and UPGMA index), and species richness among regions with an index of taxonomic diversity.Key results: In the BTS of Hidalgo, 12 families, 32 genera, 66 species and a fern hybrid were identified, as well as one family, one genera, and six species of lycopods. The families with the largest number of genera were Pteridaceae (9) and Polypodiaceae (6). The genera with the highest species richness were Anemia and Selaginella, with six species each. The widely distributed species were Adiantum tenerum and Tectaria heracleifolia (constancy of 85%). Six species were registered for the first time in the state. The floristic similarity between municipalities was high, except Huehuetla, located in the southern end of the study area. The BTS of Hidalgo occupies the third place in species per unit area (6.58/ha), within the tropical forests of the country.Conclusions: The species richness of the BTS of Hidalgo is high with respect to other regions with the same type of vegetation in Mexico, which is relevant to implement management and conservation plans, considering the high degree of deterioration of this ecosystem by human activities.